Biblical exegesis and mystical theology in the Venerable Bede - Holder, Arthur G. (Variorum collected studies, 2024)
"Biblical Exegesis and Mystical Theology in the Venerable Bede brings together seventeen essays by Arthur Holder exploring the theology and spirituality found in Bede's biblical commentaries and homilies. The volume shows that Bede was both a masterful student of received tradition and a creative thinker concerned to address the needs and concerns of his audience of Christian pastors and teachers in the eighth-century Northumbrian church. Although Bede is best known as the author of The Ecclesiastical History of the English People, the last half-century of scholarship has demonstrated the sophistication and vast influence of his work in the fields of grammar, biblical interpretation, hagiography, poetry, computus, natural science, and theology. The chapters in this volume show how Bede's exegesis was integrally connected with his work in all those genres and with the monumental artistic productions of his monastery such as the illuminated bible manuscript known as the Codex Amiatinus. The five parts of the book deal with Bede as teacher and biblical scholar, his interpretations of the tabernacle and the temple, his commentary on the Song of Songs, his attitudes toward philosophy and heresy, and his mystical theology. This book will be of interest to students of Christian theology, mysticism, the development of biblical interpretation, and the history of early medieval England"--